Investigation of glass bonding and multi-layer deposition during filament-based glass 3D printing - Liu, Chunxin; Oriekhov, Taras; Fokine, Michael (Frontiers in Materials, 2022)
Additive manufacturing of glass is an emerging technology that is foreseen to have a big impact on glass fabrication for innovative solutions within research, as well as for industrial applications. One approach is 3D printing using glass filaments. This technique is similar to directed energy deposition (DED) of metal wires using laser melting, which is highly versatile in printing complex structures. For glass, however, the technique is still at an early stage of development. Printing complex multi-layer structures have been challenging, often resulting in poor control of print geometry, excessive evaporation, as well as low repeatability. In this work we present a systematic study of filament-based 3D printing of silica-glass using CO2-laser heating. The study focuses on the bonding width (wetting) during first-layer printing onto fused quartz substrates and during multi-layer printing, i.e., layer-to-layer bonding. The main printing parameters that have been investigated include printing speed, filament feed rate, and incident laser power. Bonding widths from 17–221 µm are achieved with 196 µm diameter fused silica filaments in single line printing. Using experimentally determined printing parameters for such filament, 3D printed objects consisting of more than 100 layers were subsequently demonstrated. The results presented here provide an approach in glass 3D printing, using the filament-based technique, enabling highly complex glass structures to be fabricated.